New Advances in Legal Translation and Interpreting - Zhao, Junfeng; Li, Defeng; Lei, Victoria Lai Cheng (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book describes interdisciplinary exploration of matters related to the translation and interpreting of legal texts. Translation of legal texts has grown exponentially since the beginning of new millennium in response to the fast-increasing volume of international trade and business as well as all sorts of other transnational activities in a myriad of spheres. International trade demands translation of trade laws and business contracts, immigration leads to rise in court interpreting services, and countries may seek to enhance their international influence through translating and making known to the world their laws and/or other legal documents. These legal translation activities occurred mostly between languages officially used in international or regional organizations, such as the United Nations and the European Union, and between the languages of major countries who exert or seek influence on international economy and law. On the other hand, rapid advances in computer technology and artificial intelligence in recent years have also brought about changes in the practices of legal translation. With changes also come problems in both theory and practice that merit our immediate attention. This edited volume highlights the newest developments in the theory, practice, and training of legal translation, with contributions from international leading researchers in this area. It will be a standard reference for anyone who is to embark on research and practice of legal translation in the twenty-first century. It is also adaptable as teaching materials for translation and interpreting training. Chapter "Translating Legal Terms at International Organisations: Do Institutional Term Banks Meet Translators' Needs?" is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.
Part I Theoretical Issues -- Chapter 1. Legal Translation: Current Issues and Challenges in Research -- Chapter 2. Multilingual Lawmaking and Legal (Un)Certainty -- Chapter 3. Interpreting in Legal Settings. Chapter 5. Legal Linguistics and legal translation -- Chapter 6. Ethics in legal translation and interpreting -- Chapter 7. Legal translation in intercultural communications -- Chapter 8. Legal translation and soft power -- Chapter 9. Popular Participation in the Japanese Legal Process -- Chapter 10. Law, State, and Society in Early Imperial China -- Chapter 11Equivalence in Legal Translation: From a sociosemiotic perspective -- Chapter 12. Evolutionary and revolutionary changes in legal terminology.-Chapter 13. Translating synonymous legal terms: A mixed-genre parallel corpus study -- Part II Methods and Practices of Legal Translation -- Chapter 14. Legal Translation and Bilingual Law Drafting in Hong Kong -- Chapter 15. Translating legal terminology and phraseology -- Chapter 16. Translating Key Terms in Company Law of Hong Kong, Mainland China -- Chapter 18. The Translation of Witness Statements -- Chapter 19. Translation of Legal Papers from Urdu to English -- Chapter 20. Translating lexical legal terms between English and Arabic -- Chapter 21. Legal Translation outsourced -- Chapter 22. Advance Preparation in court interpreting -- Chapter 23. Translation in the Shadows of Interpreting in US Court Systems: standards, guidelines and practice -- Chapter 24. US Court Interpreters Act and Its 1988 Amendment: Implications for China's Court Interpreting Legislation -- Chapter 25. Stress in Polish sworn translators and interpreters -- Chapter 26. Discourse markers in interpreter-mediated police interviews -- Part III Training Legal Translators and Interpreters -- Chapter 27. Buiding resources for court interpreters: an illustrative study on translation-oriented terminological records about Spanish criminal proceedings. -- Chapter 28. Usung audiovisual clips to allow students to practise interpreting authentic court questions -- Chapter 29. Training legal translators in the United States -- Chapter 30. Court interpreter's perceived impartiality and its pedagogical implications -- Chapter 31. Interpreter Training in Hungary: from consecutive to conference and legal interpreting -- Chapter 32 -- Curricular design and implementation of a training course for interpreters in an asylum context. .
Keywords: Translating and interpreting; Computational linguistics; Sociolinguistics; Law and the social sciences; Language Translation; Computational Linguistics; Sociolinguistics; Socio-Legal Studies